Differentiated Instruction in High School Chemistry Learning in Sampit: Implementation, Challenges, and Solutions - Fakhriyana, Anisa Rahmi; Tinus, Agus; Aisyah, Iis Siti (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study explores the implementation of differentiated instruction (DI) in chemistry learning at SMA Negeri 4 Sampit, Indonesia. Using a qualitative descriptive approach, data were collected through semi-structured interviews, classroom observations, and document analysis. Findings revealed that DI was progressively implemented across grade levels. In Grade X, differentiation was minimal, with occasional product differentiation through video experiments. Grade XI showed partial process differentiation and stronger outcomes in product differentiation, particularly when students were given the choice of posters or presentations. Grade XII demonstrated the most systematic application of DI, integrating process and product differentiation within contextual projects such as the Healthy Food Campaign. Despite these positive outcomes, challenges included teacher workload, limited resources, and difficulty in differentiating content. Students reported issues with uneven pacing, a lack of varied media, and limited product formats. Practical solutions identified include context-based learning, reusable product templates, low-cost media, scaffolding, and expanded product choice. These findings contribute to the global discourse on inclusive science education by demonstrating that product differentiation and contextual strategies are effective entry points for implementing DI in resource-limited settings.